Challenges and Opportunities in Preserving Key Structural Features of 3D-Printed Metal/Covalent Organic Framework - Liu, Ximeng; Zhao, Dan; Wang, John (Nano-Micro Letters, 2024)
Metal–organic framework (MOF) and covalent organic framework (COF) are a huge group of advanced porous materials exhibiting attractive and tunable microstructural features, such as large surface area, tunable pore size, and functional surfaces, which have significant values in various application areas. The emerging 3D printing technology further provides MOF and COFs (M/COFs) with higher designability of their macrostructure and demonstrates large achievements in their performance by shaping them into advanced 3D monoliths. However, the currently available 3D printing M/COFs strategy faces a major challenge of severe destruction of M/COFs’ microstructural features, both during and after 3D printing. It is envisioned that preserving the microstructure of M/COFs in the 3D-printed monolith will bring a great improvement to the related applications. In this overview, the 3D-printed M/COFs are categorized into M/COF-mixed monoliths and M/COF-covered monoliths. Their differences in the properties, applications, and current research states are discussed. The up-to-date advancements in paste/scaffold composition and printing/covering methods to preserve the superior M/COF microstructure during 3D printing are further discussed for the two types of 3D-printed M/COF. Throughout the analysis of the current states of 3D-printed M/COFs, the expected future research direction to achieve a highly preserved microstructure in the 3D monolith is proposed. Highlights: 1 A comprehensive investigation on the research states of 3D-printed metal/covalent organic frameworks (M/COFs) is conducted with the discussion on the M/COF-mixed monolith and M/COF-covered monolith separately. 2 Recent advances in design strategies regarding both the paste/scaffold formation and the 3D-printing/covering process for preserving the better structural features of M/COFs (surface area, porosity, and micromorphology) in their 3D printed monolith are overviewed and discussed.